Study of the Relationship between Islamic Leadership Model and Tendency towards Entrepreneurship among the Ministry of SAMT Staff - AFSHARI, HOSEIN; JAGHARQ, SEYED ABDULLAH SAJADI (The journal of contemporary issues in business and government, 2021)
Nowadays, in order to manage the emerging crises in the organizations and successfully adapt to the changes and evolutions, organizations need to encourage their actors to be creative, innovative, risk-taking, responsible, and ultimately entrepreneurial. According to the thinkers, Islamic leadership, with components such as delegation of authority and responsibility, discipline and seriousness, consultation and decision-making is a key factor to entrepreneurship in the organizations. Therefore, the aim of this research is to study the relationship between Islamic leadership model and tendency towards entrepreneurial among the staff of the SAMT Ministry. The research method is a survey and the statistical population includes 1873 employees, of whom 320 people have been selected as a sample of study based on simple random sampling method. Findings indicate that there is a significant direct correlation between the managers’ Islamic leadership model and the tendency of employees towards entrepreneurship. Also, the level of the Islamic leadership model followed by the managers could explain 30% of the changes made by the staff’s tendency towards entrepreneurship.